2013
DOI: 10.1007/s13318-013-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression levels of tight junction components during reconstruction of tight junction from mucosal lesion by intestinal ischemia/reperfusion

Abstract: Tight junction (TJ) is composed of the most apical components of the intercellular junctional complex in epithelial cells; TJ has cell polarity and functions as a major determinant of epithelial barrier function. In this study, to clarify the components of TJ required for its reconstruction and functional acquisition, we examined the changes in intestinal mucosal structure that depended on mucosal lesion by intestinal I/R, that is, the changes in mRNA and protein expression of the claudin family and scaffold p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Studies have found that the pro-inflammatory cytokines TNF-α and IL-1β play a central role in an increase in intestinal epithelial TJ permeability [26,27]. Loss of tight junction proteins due to IIRI affects intestinal epithelial barrier function [28,29]. The results of this experiment on the TJ proteins prove this point of view.…”
Section: Discussionsupporting
confidence: 53%
“…Studies have found that the pro-inflammatory cytokines TNF-α and IL-1β play a central role in an increase in intestinal epithelial TJ permeability [26,27]. Loss of tight junction proteins due to IIRI affects intestinal epithelial barrier function [28,29]. The results of this experiment on the TJ proteins prove this point of view.…”
Section: Discussionsupporting
confidence: 53%
“…Trophozoites degraded all proteins tested except claudin-4 and tubulin (Figures 7A,B ), confirming that distinct trophozoites molecules produce dissimilar effect on host cell proteins. Intriguingly, trophozoites degraded occludin; although they did not affect paracellular flux in Caco-2 cells (Figure 3 ), possibly, claudin-4, a molecule that also regulates paracellular flux (Takizawa et al, 2014 ; Khan and Asif, 2015 ) performed a compensatory effect in this function, given that it was not affected by trophozoites.…”
Section: Resultsmentioning
confidence: 95%
“…This is consistent with the increased gut TJ disruption observed in IBD patients as well as the barrier defect after the disruption. It is worth mentioning that the TJ is mainly composed of zonula occludens (ZO) proteins, transmembrane proteins (junctional adhesion molecules, occludins, and claudins), and cytoskeletal structures [ 23 ]. In conclusion, the integrity of the intestinal mechanical barrier function can resist the invasion of IBD, and the inflammatory response of IBD can further damage the mechanical barrier function.…”
Section: The Pathogenesis Of Inflammatory Bowel Diseasementioning
confidence: 99%